Myelin Oligodendrocyte Glycoprotein as an Autoantigen in Inflammatory Demyelinating Diseases of the Central Nervous System - Eliseeva, Daria D.; Zakharova, Maria N. (Biochemistry (Moscow), 2023)
Demyelinating diseases of the central nervous system are caused by an autoimmune attack on the myelin sheath surrounding axons. Myelin structural proteins become antigenic, leading to the development of myelin lesions. The use of highly specialized laboratory diagnostic techniques for identification of specific antibodies directed against myelin components can significantly improve diagnostic approaches. Myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) currently includes demyelinating syndromes with known antigens. Based on the demonstrated pathogenic role of human IgG against MOG, MOGAD was classified as a distinct nosological entity. However, generation of multiple MOG isoforms by alternative splicing hinders antigen detection even with the most advanced immunofluorescence techniques. On the other hand, MOG conformational changes ensure the structural integrity of other myelin proteins and maintain human-specific mechanisms of immune autotolerance.